PENGARUH KEPERCAYAAN, KEMUDAHAN, KERAGAMAN PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN HIJAB MEREK HIJAB PRICESS (Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Islam Malang Angkatan 2013-2016 Pengguna Media Sosial Instagram ) - Atik Nisaul Kamilah; Muhammad Hufron; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT                This study aims to determine the effect of trust, ease, diversity of products and lifestyles to the purchase kepijan Hijab brand hijab princess. To be able to achieve that goal used multiple linear regression analysis, F-test & t test. Methods of data collection in this study using questionnaires distributed to all Students Faculty of Economics, Islamic University of Malang force 2013-2016 Social Media Instagram Users. The population in this study is all students of the Faculty of Economics, Islamic University of Malang force 2013-2016 Users Social Media Instagram. The use of samples using incidental sampling method, based on chance, obtained 68 respondents who became the sample in this study. Based on the results of analysis and discussion, it can be concluded that simultaneously the trust, ease, diversity of products and lifestyle significantly influence purchasing decisions. While the partial trust, product diversity and lifestyle have a significant positive effect on purchasing decisions and partially ease no significant effect on purchasing decisions Keywords: Trust, Ease, Product Diversity, Lifestyle, and Purchase Decision.